Do Employers Prefer Undocumented Workers? Evidence from China's Hukou System - Peter J. Kuhn; Kailing Shen (Institute for the Study of Labor (IZA), 2014)
We study urban Chinese employers' preferences between workers with and without a local residence permit (hukou) using callback information from an Internet job board serving private sector employers. We find that employers prefer migrant workers to locals who are identically matched to the job's requirements; these preferences are especially strong at low skill levels. We argue that migrants' higher work hours and effort help to account for employers' preferences, and present evidence that efficiency wage and intertemporal labor substitution effects might explain these hours/effort gaps.
Keywords: O15; R23; 330; temporary migration; China; hukou; undocumented migrants